ANALYSIS OF MATHEMATICS PROBLEMS IN THE 2013 CURRICULUM AND CAMBRIDGE CURRICULUM MATHEMATICS TEXTBOOKS - Ratu Sarah Fauziah Iskandar; Aji Raditya; Trisna Roy Pradipta (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Several factors influence the success of learning; one of them is the quality of textbooks. Textbooks have a pivotal role in learning, namely, representing the teacher's explanation in front of the class. Curricula have continuously changed because they are far from the expectations. In Indonesia, many schools have implemented an international curriculum to improve school quality. One of the curricula used is the Cambridge curriculum. This study analyzed the types of problems in the Cambridge and 2013 curriculum mathematics textbooks, especially on quadratic equations. This research utilized a six-dimensional analysis method which consists of mathematical activities, complexity level, answer form, contextual features, response types, and mathematical features. Furthermore, the data collection technique was carried out by analyzing and describing the types of questions in the 2013 curriculum and the Cambridge curriculum mathematics textbooks. The analysis focused on the quadratic equation topic in the 2013 curriculum and the Cambridge curriculum mathematics textbooks. The results shows that there is no difference between the types of problems in the 2013 curriculum and the Cambridge curriculum mathematics textbooks for quadratic equation topics. The framework of this study could be a reference for further research and used by mathematics textbook writers to create more diverse types of questions.